Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1051/0004-6361/202141312
|View full text |Cite
|
Sign up to set email alerts
|

The Close AGN Reference Survey (CARS)

Abstract: Context. Active galactic nuclei (AGN) are thought to be intimately connected with their host galaxies through feeding and feedback processes. A strong coupling is predicted and supported by cosmological simulations of galaxy formation, but the details of the physical mechanisms are still observationally unconstrained. Aims. Galaxies are complex systems of stars and a multiphase interstellar medium (ISM). A spatially resolved multiwavelength survey is required to map the interaction of AGN with their host galax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 301 publications
1
34
0
Order By: Relevance
“…As part of the Close AGN Reference Survey (CARS, Husemann et al 2022) 2 Mrk 1044 has been observed with the Wide Field Mode (WFM) of the MUSE instrument. The data were reduced using the standard ESO pipeline v.2.8.1 (Weilbacher et al 2012(Weilbacher et al , 2020 as described in Husemann et al (2022). The resulting data cube has a FOV of 62 .…”
Section: Vlt Muse Wfmmentioning
confidence: 99%
See 4 more Smart Citations
“…As part of the Close AGN Reference Survey (CARS, Husemann et al 2022) 2 Mrk 1044 has been observed with the Wide Field Mode (WFM) of the MUSE instrument. The data were reduced using the standard ESO pipeline v.2.8.1 (Weilbacher et al 2012(Weilbacher et al , 2020 as described in Husemann et al (2022). The resulting data cube has a FOV of 62 .…”
Section: Vlt Muse Wfmmentioning
confidence: 99%
“…Therefore, the subtraction from the original datacube causes an over-subtraction in the center. We follow the AGN-host deblending approach described in Husemann et al (2022) where the AGN spectrum is iteratively corrected for the host galaxy contribution. Thereby we assume a constant host galaxy surface brightness within the innermost 0 .…”
Section: Iterative Agn-host Deblending From the Ifu Datamentioning
confidence: 99%
See 3 more Smart Citations